Pessary or progesterone to prevent preterm birth in women with short cervical length: protocol of the 4–6 year follow-up of a randomised controlled trial (Quadruple-P) - van Limburg Stirum, Emilie V J; van der Windt, Larissa I; van Dijk, Charlotte E; van Baar, Anneloes L; Leemhuis, Aleid G; van Wely, Madelon; de Boer, Marjon A; van 't Hooft, Janneke; Oudijk, Martijn A; Pajkrt, Eva (BMJ open, 2022)
Vaginal progesterone and a cervical pessary are both interventions that are investigated for the prevention of preterm birth (PTB). Thus far, beneficial or harmful effects of these interventions on long-term child health and development are described, but evidence is not robust enough to draw firm conclusions. With this follow-up study, we intent to investigate if progesterone or a pessary is superior for the prevention of PTB considering the child's health at 4-6 years of corrected age. This study is a follow-up study of the Quadruple-P trial; a multicentre, randomised clinical trial (NL42926.018.13, Eudractnumber 2013-002884-24) which randomises women with an asymptomatic midtrimester short cervix to daily progesterone or a pessary for the prevention of PTB. All children born to mothers who participated in the Quadruple-P study (n=628 singletons and n=332 multiples) will be eligible for follow-up at 4-6 years of corrected age. Children will be assessed using parental questionnaires. Main outcomes are child (neuro)development and behaviour. Other outcomes include child mortality, growth and general health. A composite of adverse child outcomes will be compared between the progesterone and pessary groups reporting OR and the corresponding 95% CI. Analyses will be performed separately for singletons and multiples and using the intention-to-treat approach. The Medical Research Ethics Committee from Amsterdam UMC confirmed that de Medical Research Involving Human Subjects Act (WMO) did not apply to our study (W20_481 #20.531). Results will be published in a peer-reviewed journal and shared with stakeholders and participants. This protocol is published before analysis of the results. Dutch Trial Register (NL9646).